Laparoscopic repair of a combined transmesocolic, transomental hernia - Kulkarni, Gaurav V. (J Minim Access Surg, 2020)
Transmesocolic and transomental hernias (TOHs) are rare types of internal hernia. Both these hernias occurring concurrently in a patient are even rarer. We report a patient with signs of recurrent small-bowel obstruction who was found to have a dual transmesocolic, TOH. Computed tomography imaging and subsequent laparoscopic exploration identified small-bowel loops passing through a defect in the transverse mesocolon behind the stomach to emerge through the gastrohepatic omentum. This was treated successfully by laparoscopy. To the best of our knowledge, this is the first reported case of a combined transmesocolic, TOH undergoing successful laparoscopic repair.